2022
DOI: 10.1108/jsfe-11-2021-0069
|View full text |Cite
|
Sign up to set email alerts
|

Some recent developments and testing strategies relating to the passive fire protection of concrete using intumescent coatings: a review

Abstract: PurposeIn the present article, the authors have conducted a review on some of the recent developments given in the literature pertaining to the passive protection of concrete structures using intumescent coatings. Here, the main thrust is placed on the spalling phenomenon of concrete elements when exposed to elevated temperatures and fires.Design/methodology/approachIn this context, it has been long established that prolonged thermal insult on concrete members will lead to egress of water, both physically boun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 93 publications
1
2
0
Order By: Relevance
“…This does not differ from the practical data, well known from works [1,3,5], the authors of which, by the way, also associate the effectiveness of fire protection with the formation of a foam coke layer under the influence of the burner flame. But, in contrast to the results of research reported in [6,7,18,19], our data on the effect of the swelling coating on the process of retarding the transfer of temperature allow us to state the following:…”
Section: Discussion Of Results Of Studying the Process Of Formation O...supporting
confidence: 56%
See 1 more Smart Citation
“…This does not differ from the practical data, well known from works [1,3,5], the authors of which, by the way, also associate the effectiveness of fire protection with the formation of a foam coke layer under the influence of the burner flame. But, in contrast to the results of research reported in [6,7,18,19], our data on the effect of the swelling coating on the process of retarding the transfer of temperature allow us to state the following:…”
Section: Discussion Of Results Of Studying the Process Of Formation O...supporting
confidence: 56%
“…In article [3], authors reviewed some recent developments in the literature regarding the passive protection of concrete structures using intumescent coatings. Although spalling of concrete structures has long been recognized as a serious problem that can often lead to catastrophic infrastructure failure, the utility of intumescent pavement as a mitigation strategy is new and understudied.…”
Section: Literature Review and Problem Statementmentioning
confidence: 99%
“…The coating can be applied to various substrates, such as polymeric materials, textiles, wood [2], and metals. They are the preferred choice for passive fire protection because they offer aesthetic appearance, flexibility, quick application, and ease of inspection and maintenance [3].…”
Section: Wpływ Krzemionki Na Właściwości Pęczniejących Powłok Ognioch...mentioning
confidence: 99%